Overall and chemotherapy‐free survival following stereotactic body radiation therapy for abdominopelvic oligometastases. Issue 4 (4th June 2020) - Shahi, Jeevin; Peng, Jonathan; Donovan, Elysia; Vansantvoort, Jasmin; Wong, Raimond; Tsakiridis, Theodoros; Quan, Kimmen; Parpia, Sameer; Swaminath, Anand
Abstract: Introduction: Limited data establish the efficacy and safety of SBRT in the abdominopelvic (AP) space, where SBRT delivery is challenging due to the proximity of radiosensitive luminal gastrointestinal (GI) organs. The aim of this study was to assess clinical outcomes in patients with AP OM treated with SBRT. Methods: Eligible patients were those with OM (defined as metastases in ≤3 total sites) in the AP space (excluding liver) treated with SBRT. Descriptive statistics and Kaplan–Meier estimates of (LC), progression‐free survival (PFS), overall survival (OS) and chemotherapy‐free survival (CFS) were performed. Results: Fifty‐one patients with 58 AP OM received SBRT between 2011 and 2015. Median follow‐up was 21.9 months. All SBRT treatments were delivered in 5 fractions with a median dose of 35 Gy (25–40 Gy). Progression post‐SBRT occurred in 38/51 patients (75%), with a median PFS of 4.9 months (95% CI: 2.5–7.5), and 2‐year PFS of 29%. Rates of 2‐and 4‐year LC were 74% and 69%, respectively. Median OS was 42.6 months (95% CI: 31–55). Oligometastatic progression occurred in 21/38 patients, and of those, 48% (10/21) received further SBRT. Resulting 2‐ and 4‐year CFS were 47% and 37%, respectively (median 15.1 months). Nineteen patients (37%) experienced a grade 1 or 2 acute toxicity. One grade 3 (acute) toxicity was observed. No grade 4 or 5 toxicities were detected. Conclusions: SBRT to AP OM was associated with sustained LC, excellent OS and minimal toxicity. The use of SBRT allowed for prolonged CFS and the salvage of limited‐burden distant failures.